Epidemiology, risk factors and strategies for the prevention of global unintentional fatal drowning in people aged 50 years and older: a systematic review - Peden, AE (2017)
Purpose: Drowning is a global public health issue and prevention poses an ongoing challenge for all countries. Many nations are experiencing ageing populations, and little is known about the epidemiology, risk factors and prevention of drowning deaths among older people. This paper reports on a systematic review of literature published on drowning among older people. Methods: A systematic literature review was undertaken using English-language, Portuguese-language and Spanish-language papers published between 1980 and 2015. The review explores gaps in the literature with a focus on the epidemiology, risk factors and strategies for the prevention of unintentional fatal drowning among people 50 years and over. Results: Thirty-eight papers were deemed relevant to the study design, including 18 (47%) on epidemiology, 19 (50%) on risk factors and 9 (24%) on strategies for prevention. Risk factors identified included male gender, ethnicity, rurality and increasing age. Prevention strategies commonly proposed were education and wearing life jackets. Gaps identified in the published literature include a lack of consistency around age groupings used for epidemiological studies; a lack of consensus on risk factors; a lack of total population, country-level analysis; and the need for older age-specific prevention strategies that have been implemented and their effectiveness evaluated. Conclusion: This review identified drowning deaths among older people as a global issue. Further work is required to reduce drowning in this cohort. High-quality epidemiological studies identifying risk factors using standardised age groupings to allow for international comparisons are required, as are implementation and evaluation of older age-specific prevention strategies.